2000
DOI: 10.1007/pl00011179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Finnish Versions of the Functional Indices BASFI and DFI in Spondylarthropathy

Abstract: The aim of the study was to compare and evaluate the usefulness of Finnish versions of two functional indices used in spondylarthropathies. Seventy consecutive inpatients with different kinds of spondylarthropathies filled in self-administered questionnaires: the Bath Ankylosing Spondylitis Functional Index (BASFI) and the Dougados Functional Index for spondylarthropathies (DFI). Cronbach's alpha as a coefficient of internal consistency was analysed for BASFI and DFI. Test-retest reliability was evaluated in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 9 publications
0
14
0
2
Order By: Relevance
“…11 These results are also in line with another study that applied the BASFI (self-administered approach in D1 and D2) and their results showed also an excellent reliability (ICC = 0.99). 15 In addition, the test-retest reliability of BASFI was good, with a high intraclass correlation coeffi cient between the two time points (24 hours interval, ICC = 0.93). 13 In opposite direction, a Mexican-Spanish version found worse results than the studies described above.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…11 These results are also in line with another study that applied the BASFI (self-administered approach in D1 and D2) and their results showed also an excellent reliability (ICC = 0.99). 15 In addition, the test-retest reliability of BASFI was good, with a high intraclass correlation coeffi cient between the two time points (24 hours interval, ICC = 0.93). 13 In opposite direction, a Mexican-Spanish version found worse results than the studies described above.…”
Section: Discussionmentioning
confidence: 90%
“…In the Finnish study only DFI showed correlation with age. 13,15 However, the BASFI Chinese version showed weak correlations both with age and disease duration. 22 In fact, it is possible that not only age but other variables combined result in disease severity and functional disability so that, as a consequence, a patient could be older but with less severe disease, while a younger patient could have more severe disease.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Each item is answered on a 10-cm horizontal visual analogue scale (VAS) [2,3,5,6,9,11]. Total scores range from 0 to 10, with higher scores indicating more severe impairment.…”
Section: Methodsmentioning
confidence: 99%